Lavender - Soon, Jennifer Beiyu (2017)
“Lavender” is an experimental short film. The project explores surrealist interpretation of life in one’s mind, journey of rebirths in a dreamlike environment, and the incorporation of mellow, nostalgic and atmospheric sound. The visuals and sounds meld together to trigger an emotional journey. It is an ardent love of life through it’s ups and downs, an experience through metaphysical worlds of our inner consciousness. It is a collection of symbols and metaphors about life and rebirths. The film is traditional 2D animation but uses 3D models and video footage as guides for realistic details. There is more stylistic designs reminiscent of Japanese woodblock printing incorporated with contemporary designs. The decision to use completely hand-drawn animation with limited colours is to preserve the raw expressive lines, using it to translate most of the emotion. As the linework will be the highlight of the animation, muted colours are used to prevent clashing of visual identity. All these visual considerations come together to make up the art of Lavender.